«ЖӘҲАНША» ДӘСТАНЫНЫҢ ҚУРБАНБАЙ ЖЫРАЎ РЕПЕРТУАРЫНДА ЖЫРЛАНЫЎЫ - Мамбетов, Ж.Қ. (ILIM hám JÁMIYET, 2021)
The article deals with the Kurbanboy Jirov version of the Karakalpak folk epic "Jahansho". Kurbanbay Jirov's skill is demonstrated in narrating the plot and enhancing the art. The individual talent of Kurbanboy Jirov is explored in depicting the events in the epic.